Mathematical model of a kidney dialyser - Segaran, Tina R. (2014)
Hemodialysis is a technique of removing waste materials and extra fluids (creatinine and urea) from the blood of kidney patients. A mathematical model of an artificial kidney dialysis machine (dialyser) is used to analyse the clearances of waste materials against the flow rate of the blood. The mathematical model is formulated using the theory differential equations. The clearance of creatinine and urea versus the flow rate of the blood are calculated as solution to the model. The graphs of the solution are plotted using Maple 12 software and compared with experimental data. We find that the calculated clearances of creatinine and urea against the rate of blood flow with experimental data are much closed.